Motivation of first-time, repeat, and serial backpackers: a Malaysian perspective - Abdul Latif, Samshul Amry; Ismail, Nuraini (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh Campus, 2019)
The objectives of this study are to identify the main travel motivations of Malaysian backpackers and to investigate the differences in travel motivations between different groups of backpackers namely; first-time, repeat, and serial backpackers. This study used convenience sampling approach, and the data were obtained through self-administered online survey of Malaysian backpackers. Based on a sample of 249, the non-normally distributed data were analysed using exploratory factor analysis (EFA), assessment of median scores and Kruskal-Wallis H tests. The findings show that the main factor which motivates Malaysian backpackers to go on a backpacking trip is stimulation (push), while the least is recognition (push). The results also indicated that there are differences in Malaysian backpackers’ motivation based on their travel experience level. The limitation of the study is that the samples are skewed toward females, and the majority (87%) are aged between 21 and 35 years old.